Vocabulary Enrichment through Mnemonics technique for Young Learners In Smart and Fun English Course - Dedi Setiawan; Saraka; Anjar Dwi Astuti (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2020)
The purposes of this study were to describe the implementation of teacher’s strategies in teaching English vocabulary to young learners for young learners, and to describe the problems of the implementation of teacher’s strategies in teaching English vocabulary for young learners. The design of this study was a qualitative descriptive design by using observation and interview. The research subject of this study was the English teacher who taught the Primary-Intermediate classes at SMART AND FUN English course in Samarinda. To collect and to analyze the data, an interactive data analysis was used. The study revealed the following findings: the researcher found out that the the teacher has already grasped the concept of mnemonics techniques, and tried to use one of them (cards that contain pictures) The use of picture itself is included as the visual mnemonics technique, which makes use of visual aids in teaching vocabularies. The researcher also found out that the teacher has understood the theory of mnemonics technique, based on the statement that he provided at least two techniques – pictures for low-level students and storytelling for high-level ones. The research subject then claimed that he had already tried to implement two kinds of technique, called pictures and storytelling. However, based on the interview from this study, the research subject claimed that the teacher must have knowledge about the concept of memorization in order to understand the mnemonics technique. In addition, the research subject also stated that using mnemonics technique take a certain amount of time, then suggesting the teachers to be prepared well before using the techniques. The researcher concluded that the mnemonics technique is a good way for English teachers to be implemented in future teachings. The mnemonics technique is one of many techniques to teach vocabularies to the students, however, it can be done in many ways that deals with creativity, such as the use of pictures, drilling, storytelling etc. Hopefully, the English teachers do not have to be confused if they want to teach vocabularies, even the particular ones to the students by taking benefits from using mnemonics technique.